The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1088/2053-1591/ac8857
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of plasma spray process variables to attain the minimum porosity and maximum hardness of the LZ/YSZ thermal barrier coatings utilizing the response surface approach

Abstract: Lanthanum zirconate (LZ) has emerged as a novel thermal barrier coating (TBC) material because of its higher temperature phase stability, and low sintering ability than the current standard yttria-stabilized zirconia (YSZ). In order to combine the advantages, LZ and YSZ feedstock powders are blended with predetermined weight ratios (50:50) as composite coatings. The leading issue in developing the composite coating using the atmospheric plasma spray method (APS) is finding the optimum range of input parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As can be seen from Table 3, the porosity of the 15 groups of experiments ranged from 1.80% to 6.48%, and the overall change was obvious, which indicated that changing the combination of parameters within a reasonable range had a more obvious impact on the porosity of the coatings. In order to verify the adequacy of the model [18], the analysis of variance (ANOVA) of the model was shown in Table 4.…”
Section: Rsm Modelling and Analysismentioning
confidence: 99%
“…As can be seen from Table 3, the porosity of the 15 groups of experiments ranged from 1.80% to 6.48%, and the overall change was obvious, which indicated that changing the combination of parameters within a reasonable range had a more obvious impact on the porosity of the coatings. In order to verify the adequacy of the model [18], the analysis of variance (ANOVA) of the model was shown in Table 4.…”
Section: Rsm Modelling and Analysismentioning
confidence: 99%
“…Для дослідження багатофакторних систем найбільш доцільним є використання статистичних методів планування експерименту [13,14]. Під плануванням експерименту розуміють процес визначення кількості та умов проведення дослідів, необхідних і достатніх для вирішення поставленої задачі з достатньою точ-ністю.…”
Section: аналіз досліджень та публікаційunclassified
“…These products are the first of their kind, developed in a variety of forms using natural fibers. Krishnudu et al [23] examined the optimization of the reinforcement ratios, and the optimum values of reinforcement are recommended in order to increase the mechanical characteristics [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%